‘I have no love for such people, because they leave us to suffer’: a qualitative study of health workers’ responses and institutional adaptations to absenteeism in rural Uganda - Raymond Tweheyo; Catherine Reed; Stephen Campbell; Linda Davies; Gavin Daker-White (BMJ Global Health)
Background Achieving positive treatment outcomes and patient safety are critical goals of the healthcare system. However, this is greatly undermined by near universal health workforce absenteeism, especially in public health facilities of rural Uganda. We investigated the coping adaptations and related consequences of health workforce absenteeism in public and private not-for-profit (PNFP) health facilities of rural Uganda.Methods An empirical qualitative study involving case study methodology for sampling and principles of grounded theory for data collection and analysis. Focus groups and in-depth interviews were used to interview a total of 95 healthcare workers (11 supervisors and 84 frontline workers). The NVivo V.10 QSR software package was used for data management.Results There was tolerance of absenteeism in both the public and PNFP sectors, more so for clinicians and managers. Coping strategies varied according to the type of health facility. A majority of the PNFP participants reported emotion-focused reactions. These included unplanned work overload, stress, resulting anger directed towards coworkers and patients, shortening of consultation times and retaliatory absence. On the other hand, various cadres of public health facility participants reported ineffective problem-solving adaptations. These included altering weekly schedules, differing patient appointments, impeding absence monitoring registers, offering unnecessary patient referrals and rampant unsupervised informal task shifting from clinicians to nurses.Conclusion High levels of absenteeism attributed to clinicians and health service managers result in work overload and stress for frontline health workers, and unsupervised informal task shifting of clinical workload to nurses, who are the less clinically skilled. In resource-limited settings, the underlying causes of absenteeism and low staff morale require attention, because when left unattended, the coping responses to absenteeism can be seen to compromise the well-being of the workforce, the quality of healthcare and patients’ access to care.